Analysis of the Implementation of Building Information Modeling (BIM) at the Ministry of Public Works and Housing (MPWH) - RAKHMAN, NOFA FATKHUR; TENRISUKI TENRIAJENG, ANDI (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2026)
BIM has been integrated across various project phases, from planning and execution to operations and maintenance. Despite its growing adoption, limited studies have systematically measured BIM maturity within Indonesia’s public sector, particularly under the Ministry of Public Works and Housing (MPWH). This study, therefore, seeks to fill that gap by evaluating the extent of BIM implementation in construction projects, with a focus on its effectiveness in enhancing cost efficiency, quality, and time management. A descriptive research method was applied, using manual data analysis derived from internal monitoring reports, questionnaire responses, and literature reviews. The level of BIM implementation was assessed across three core dimensions: technology, processes, and policy frameworks. These were measured using the BIM Maturity Index (BIMMI), which showed maturity levels ranging from “Managed” to “Integrated,” depending on the sub-category. On average, BIM adoption within the ministry is categorized at the “Managed” level, with a BIMMI score of 55%. Readiness across technological infrastructure, operational procedures, and regulatory frameworks varies widely among organizational units. For instance, the Directorate General of Highways (DGH) achieved an “Optimised” level with a score of 83% and could serve as a national benchmark. In comparison, the Directorate General of Human Settlements (DGHS) reached an “Integrated” level at 73%. In contrast, the Directorate General of Water Resources (DGWR) and the Directorate General of Housing (DGH) showed much lower maturity levels, at 37% and 13% respectively, particularly in contractual policy readiness, which remains at an “Ad-hoc” level (27%). The findings highlight a research question central to this study: How do variations in policy readiness and technological infrastructure influence BIM maturity across MPWH units? The results support the hypothesis that policy readiness is the most decisive factor limiting BIM integration, offering novel insights for designing targeted national strategies to accelerate BIM adoption.